Predictors and long-term clinical outcomes of newly developed atrial fibrillation in patients with cardiac implantable electronic devices. Issue 28 (July 2016) - Kim, Bum Sung; Chun, Kwang Jin; Hwang, Jin kyung; Park, Seung-Jung; Park, Kyoung-Min; Kim, June Soo; On, Young Keun
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: To evaluate predictors and long-term prognosis of atrial fibrillation (AF) following cardiac implantable electronic device (CIED) implantation in patients without history of AF. Methods: From May 1994 to April 2014, 1825 patients with CIED were enrolled in a retrospective, single-center registry. A total of 880 patients from the registry without prior documented AF history were included in the final analysis and were placed into either non-detected AF (NDAF) group or CIED-detected AF group according to development of AF over a follow-up period of 7 years. AF development was defined as any paroxysmal atrial tachyarrhythmia (atrial rate ≥ 180 beats/min) lasting at least 5 minutes according to CIED records. Results: Overall, 122 (13.8%) of the 880 patients experienced new development of AF during follow-up period. According to multivariate analysis, the independent predictors for development of AF were prior heart failure (hazard ratio [HR], 2.40; 95% confidence interval [CI], 1.50–3.85; P < 0.001), prior sinus node dysfunction (HR, 2.33; 95% CI, 1.62–3.55; P < 0.001), and left atrium volume index of 38.5 mL/m 2 or more (HR, 2.01; 95% CI, 1.23–3.30; P = 0.005). In CDAF group, the risk of heart failure readmission (adjusted HR, 3.79; 95% CI, 1.99–7.22; P < 0.001) and stroke readmission (adjusted HR, 5.33; 95% CI, 1.58–17.97; P = 0.007) was higher than in nondetected AF group. Conclusion: In patients with CIED, prior history of heart failure, sinus node dysfunction, and LA volume index ≥38.5 mL/m 2 were independent predictors of new AF cases. Newly developed AF was significantly associated with increased risk of HF and stroke readmission, according to long-term follow up.